SELECTION OF UNMANNED AIRCRAFT VEHICLE (UAV) TO IMPROVE EARLY DETECTION IN SUPPORTING SECURITY OPERATIONS IN THE NATUNA SEA BASED ON MEASURE OF EFFECTIVENESS (Tunas Geografi, 2022)
Technological developments in addition to bringing positive impacts also have negative impacts in the form of factual threats and potential threats to Indonesian marine security. The ability to detect and prevent early against these threats absolutely must be mastered by security and defense institutions or institutions in the marine sector. One of the efforts in collecting maritime data is to utilize Unmanned Aircraft Vehicle (UAV) technology. UAV technology has developed rapidly and is widely used in civilian and military circles, such as: early detection, intelligence surveillance and reconnaissance (ISR), image and video capture, Search and Rescue (SAR), and various reconnaissance and monitoring missions. The Indonesian Navy as a state instrument carrying out the task of state defense at sea has maritime operations capabilities that must continue to be developed. This study uses a descriptive quantitative approach, with the MoE method to assess the effectiveness of the use of UAV in Indonesian Navy intelligence and the AHP method to select the best type of UAV. The results of the effectiveness measurement obtained by UAV are declared effective in supporting the Navy's security operations. The results of data processing for the selection of the best UAV which is ranked first recommended to be held is the UAV type of High Altitude Long Endurance (HALE) which has strategic capabilities. It is hoped that by having UAV type HALE the TNI Al's operational pattern will be more effective and security can be increased optimally